Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa - Auma, Joseph; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Livestock production is a major livelihood in many parts of Africa, providing multiple benefits and uses that include milk, meat, payment of dowry, measure of wealth, draft power among others. In particular, extensive livestock systems support most of Africa’s livestock population, with 63%, 82% and 70% of the continent’s cattle, sheep and goats, respectively. Mostly, they are raised in climate-sensitive arid and semi-arid areas of Africa in subsistence level rain-fed systems. These systems experience environmental (land, water, ecosystem) degradation, economic (low investment, lack of access to inputs, credit, markets) and human and institutional capacity (poor infrastructure, advisory services) related constraints, often exacerbated by extreme weather events and climate change. As a result, shortage of feedstock is common, coupled with poor health and highly variable and low productivity. In Eastern and Southern African (ESA) countries, pastoralists and agro-pastoralists face critical challenges, including an inability to meet food and nutrition security (FNS) needs, and diminishing resilience and adaptive capacity against frequent climate (water and heat stress, droughts, diseases) and non-climate related shocks (economic shocks, conflict, migration). While livestock offers multiple benefits and uses, they are the largest source of agricultural greenhouse gas (GHG) emissions in Africa, accounting for almost 80% of total agricultural emissions, and growing by about 3% per year. This project aims to support stakeholders engaged in extensive livestock systems in Eastern and Southern Africa to design and implement scalable sustainable interventions that promote adaptive capacity and food and nutrition security of men and women livestock keepers, while reducing GHG emissions from livestock production.